FISHERY AND STOCK STATUS OF BLUE SWIMMER CRAB, PORTUNUS PELAGICUS (LINNAEUS, 1758) FROM PALK BAY WATERS, TAMIL NADU, INDIA - VAISHNAV, ANAND; LAL, JHAM; MEHTA , NARESH KUMAR; PRIYADARSHINI, M. BHARGHAVI; SINGH , N. SURESHCHANDRA; PATI , BIKASH KUMAR (Journal of the Inland Fisheries Society of India, 2026)
A comprehensive study was conducted from November 2019 to October 2020 in the Palk Bay region to evaluate the fishery characteristics of Portunus pelagicus. The assessment covered several important aspects, including catch per unit effort (CPUE), size distribution, stock status, and mortality rates. Data were collected from four prominent landing centers: Devipattinam, Thirupalaikudi, Moreppannai, and Karankadu, which were designated for data collection. The study found that the peak fishing season for Portunus pelagicus occurred from January to June, and the monthly average CPUE was 6.10 kg day-1. Carapace length (pooled) was measured from 30 to 92 mm and carapace width from 70 to 193 mm. The study’s estimations for the crab included a total mortality (Z) of 5.83- yrs, a natural mortality (M) of 1.87- yrs, a fishing mortality (F) of 3.97- yrs, and an exploitation ratio (E) of 0.68 years. The maximum sustainable yield (MSY) was estimated at 405 metric tons, contrasting with the current annual catch of 552 metric tons. The overall stock assessment indicated a total biomass of 813 metric tons, with an annual stock increment of 139 metric tons. To align with sustainable management objectives and achieve the MSY, a recommended reduction in fishing effort of 2.59% was proposed. These findings provide valuable insights into the conservation and management of the Portunus pelagicus fishery in the Palk Bay region.